GAMBARAN PENGGUNAAN ALAT PERMAINAN EDUKATIF PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) DI RA ROHMAWIYAH BANJARSARI KABUPATEN CIAMIS TAHUN 2018 - muhamad dadan taofik; yuyun rahayu; yanti sriyanti (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2019)
Educational Game Tools is a game tool that can provide optimum game function and child development. The recommended editing tools for children aged 4-6 years include paint colors, blocks and puzzles. Impacts that may occur if the Educational Game Tools is is not fulfilled, the process of child growth is not optimal so that the talent and potential that exist in the child is not excavated or if the child has a developmental disorder such as delay cannot be immediately known. The method in this research is descriptive, the research done to find out the value of independent variables, either one variable or more (independent) without making a comparison, or connecting with other variables. The population in this study were all parents of students aged 4-6 years in RA Rohmawiyah Banjarsari Kabupaten Ciamis academic year 2017-2018 as many as 32 people.Sampling in this study using total sampling that is the entire population used as research samples. The results showed that the use of educational games in preschool children (4-6 years) in RA Rohmawiyah Banjarsari Kabupaten Ciamis, most categorized do not use as many as 20 people (62.5%). Suggestions are expected for parents to further improve their understanding of good educational game tools and in accordance with the development of children, this understanding can be done by following the various counseling from health workers, or reading other books that have something to do with educational game tools.